2023
DOI: 10.3389/fnins.2023.1145318
|View full text |Cite
|
Sign up to set email alerts
|

Tau protein plays a role in the mechanism of cognitive disorders induced by anesthetic drugs

Abstract: Cognitive disorders are mental health disorders that can affect cognitive ability. Surgery and anesthesia have been proposed to increase the incidence of cognitive dysfunction, including declines in memory, learning, attention and executive function. Tau protein is a microtubule-associated protein located in the axons of neurons and is important for microtubule assembly and stability; its biological function is mainly regulated by phosphorylation. Phosphorylated tau protein has been associated with cognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 229 publications
0
4
0
Order By: Relevance
“…This is supported by studies that demonstrate the critical role of Tau protein in cognitive dysfunction caused by anesthetic drugs and the regulatory role of SIRT1 in Tau phosphorylation. These studies highlight that activation of SIRT1 and modulation of Tau phosphorylation can effectively alleviate cognitive dysfunction induced by anesthesia, further underscoring the potential of SYR in targeting these pathways for neuroprotection ( 4 , 20 , 21 ). The intervention with EX527, a SIRT1 inhibitor, further confirms the pivotal role of SIRT1 in mediating SYR’s protective actions against Sev-induced cognitive deficits, glial activation, and apoptotic signaling.…”
Section: Discussionmentioning
confidence: 82%
“…This is supported by studies that demonstrate the critical role of Tau protein in cognitive dysfunction caused by anesthetic drugs and the regulatory role of SIRT1 in Tau phosphorylation. These studies highlight that activation of SIRT1 and modulation of Tau phosphorylation can effectively alleviate cognitive dysfunction induced by anesthesia, further underscoring the potential of SYR in targeting these pathways for neuroprotection ( 4 , 20 , 21 ). The intervention with EX527, a SIRT1 inhibitor, further confirms the pivotal role of SIRT1 in mediating SYR’s protective actions against Sev-induced cognitive deficits, glial activation, and apoptotic signaling.…”
Section: Discussionmentioning
confidence: 82%
“…Tau protein's role in consciousness disorders, such as AD, can be analyzed in AD mouse models or in anesthetized mouse models. A correlation between tau modifications and anesthesia has been described by Chen et al (2023). Propofol-induced anesthesia may activate protein kinase-like GSK3β (Huang et al, 2016), also known as tau kinase I, and the kinase will modify tau protein at specific residues that are found in AD (Hanger et al, 2009), preventing the normal assembly of MTs.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective longitudinal study of older cardiac surgery patients found that the prevalence of dementia 7.5 years after interventions was significantly higher than the population prevalence [12]. Animal studies also indicate that surgery and anesthesia contribute to cognitive decline and AD-associated neuropathologic changes, including neuroinflammation, Aβ aggregation, and tau hyperphosphorylation [30,31].…”
Section: Pocd Risk Factors and Clinical Effectsmentioning
confidence: 99%